Rethinking the Role of Nitrogen and Phosphorus in the Eutrophication of Aquatic Ecosystems - Ashley Smyth; H. Dail Laughinghouse; Karl Havens; Thomas Frazer (EDIS, 2022)
Nitrogen and phosphorus are two nutrients that are essential for the growth and survival of plants and animals but are often present in short supply. Both nitrogen and phosphorus are applied regularly through fertilizer to increase the yield of crops needed to feed human populations and for residential and commercial landscaping purposes. This publication contains information for stakeholders, students, scientists, and environmental agencies interested in understanding how nitrogen and phosphorus affect water resources. Major revision by Ashley Smyth, H. Dail Laughinghouse IV, Karl Havens, and Thomas Frazer; 5 pp. https://edis.ifas.ufl.edu/sg118